(untitled) (Research, Society and Development, 2021)
The present work seeks to identify whether the Serra das Cordilleras de Colméia State School - TO works the theme of environmental education and sustainability in an interdisciplinary way, seeking the formation of environmentally critical and sustainable subjects, starting from the evaluation of the perception of high school students through a qualitative approach and use of the questionnaire. The data obtained in the collection were analyzed and tabulated based on a quantitative-qualitative approach, with the participation of 123 students. It was observed that 94.31% had heard about environmental education, with regard to teachers working activities related to environmental education in the classroom, 65.04% of students answered that only a few times, revealing that environmental education is not yet a topic worked in an interdisciplinary way, although the National Environmental Education Policy (PNEA) requires that the development of these activities must occur in a transversal and interdisciplinary manner in order to become an integrated, continuous and permanent educational practice, at all levels and modalities of teaching formal, adapting to current environmental needs, since this is considered to be one of the foundations for the long-awaited sustainability.